The sleeping soul doctrine of metaphysical anthropology in the Javanese death tradition - Panuntun, Daniel F. (HTS teologiese studies, 2023)
The doctrine of the sleeping soul is a doctrine developed to accommodate local wisdom in Indonesia. This doctrine describes the metaphysical part of man after death. A local pearl of wisdom discussed is the Javanese death slametan tradition. The purpose of this article is to develop the doctrine of the sleeping soul according to the narrative of Jesus’ words in Mark 5:35–42 and the Prophet Daniel in Daniel 12:1–3 in representing the metaphysical anthropological view of the Javanese death slametan tradition in terms of the theory of collective memory. The descriptions of the sleeping soul doctrine in the Javanese death slametan tradition are as follows: Firstly, there is a collective memory in giving appreciation to the metaphysical side of humans after death. Secondly, the sleeping soul doctrine is developed from the collective memory of the Javanese death slametan tradition and the Hebrew view. Thirdly, the sleeping soul doctrine is a contextualisation doctrine of the Javanese death slametan tradition.Contribution: The implications of this research give birth to the doctrine of the sleeping soul in the framework of the preservation of Javanese culture, especially in the Javanese culture of death [slametan]. This study proves that Christianity has contributed to caring for culture rather than alienating it.